2008
DOI: 10.1016/j.bone.2008.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation of bone mineral density and selected risk factors for prediction of incident fracture among Canadians 50 and older

Abstract: Background-Striking geographic variation in the incidence of osteoporotic fracture has been shown in national and international studies. The contributing risk factors for this variation are not fully understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…For the LTC cohort, our incidence rates were similar to [15,27,28] or lower than [29,30] other published studies on institutionalized populations, particularly Chandler et al who reported a rate of 109 osteoporotic fractures per 1000 person-years [31]. Our reported rates in the community were higher than the community-based Canadian Multicentre Osteoporosis Study (CaMos) [32] although there are differences in study methodologies with CaMOS relying on patient selfreport.…”
Section: Discussionsupporting
confidence: 74%
“…For the LTC cohort, our incidence rates were similar to [15,27,28] or lower than [29,30] other published studies on institutionalized populations, particularly Chandler et al who reported a rate of 109 osteoporotic fractures per 1000 person-years [31]. Our reported rates in the community were higher than the community-based Canadian Multicentre Osteoporosis Study (CaMos) [32] although there are differences in study methodologies with CaMOS relying on patient selfreport.…”
Section: Discussionsupporting
confidence: 74%
“…In older persons with osteoporosis the bone mineral density is reduced, and the bone architecture is disrupted. Osteoporosis is a disease that is more prevalent in older persons, and more prevalent among older persons in Scandinavia and the United States than elsewhere [1][2][3][4]. Several factors have been associated with an increased risk for osteoporosis, including female gender, age, ethnicity, diet, and lifestyle [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hamilton and Toronto results both required a one-time correction. Hamilton measurements were reduced by 1.5% starting in January 1998 and Toronto measurements were increased by 0.85% starting in September 1997 [13].…”
Section: Bone Mineral Densitymentioning
confidence: 99%
“…This resulted in 4194 men and women. Baseline and year five assessments included an extensive interviewer-administered questionnaire, lumbar BMD testing, and lateral lumbar and thoracic spine radiographs, in which lumbar anterior, middle, and posterior heights were measured manually [13].…”
Section: Sample Selectionmentioning
confidence: 99%